Profile of Therapy Adherence-Prolanis Related to Sociodemography: A Literature Review - Dhea Salsa Bella; Setiyo Budi Santoso; Elmiawati Latifah (Urecol Journal. Part C: Health Sciences, 2021)
The results of this literature review present a profile of measuring adherence to therapy in prolanis member. More specifically, the authors explored the adherence related to the sociodemographic variants. The literature search utilizes the Google Scholar data storage base. Researchers used two variants of keywords; (1) “prolanis” and “drug”, (2) “prolanis” and “pharmaceutical”. The literature search is limited to the results of publications during the years 2010-2020. Literature review studies only involve research results that meet the following inclusion criteria; (1) scientific articles published after going through the peer review process, (2) research involving sociodemographic variables and therapy adherence index, (3) research involving only prolanis participants, and (4) research results showing correlation values between variables. A total of 9 articles met the inclusion criteria according to the research objectives. This literature review involved 644 respondents from 12 health centers and 1 treatment center as subjects in this study. The results of our literature review confirm that prolanis participants need family support and adequate knowledge, in order to adhere to therapy. In addition, we also conclude that there is no relationship between gender differences and adherence to therapy. Based on these conclusions, we recommend community pharmacy practitioners, to optimize educational services and provide basic information about drugs, both to prolanis participants and their families. We note that researchers have not mutually agreed on the relationship between therapy adherence with age, education, type of work and home pharmacy care services in prolanis. The exploration of sociodemographic variables, which is still a matter of debate, is a priority for further research to identify adherence to prolanis therapy. We also suggest to future researchers to avoid the use of MMAS-8. The use of questionnaires without permission from the inventor is prone to licensing problems.